Fiqh Teaching Action Among Islamic Educators in Brunei Darussalam - Siti Astri Hj Moksin; Muhammad Zahiri Awang Mat; Hjh Norwati Hj Abu Bakar (International Tatho Academics, 2024)
Effective teaching is often associated with mastery of the content of the lesson and pedagogical skills. Thus, to implement effective teaching, Shulman introduced six-cycle processes of pedagogical reasoning and action that can help teachers organize their teaching. However, this study only focused on teaching action (the instruction process) in the class. Therefore, this study aims to explore the teaching practices of Fiqh teachers in religious schools. The study uses a method of qualitative research, through interviews, observation of teaching, and document analysis, to collect data. The study participants consisted of 10 Fiqh religious teachers who taught Grades IV, V, and VI. Thematic analysis was used in this study for the formation of themes and sub-themes. The results of the study found that there are several important elements for the instruction process in the cycle of pedagogical reasoning and actions in the classroom. The mastery of the teacher's pedagogical content knowledge and its application in the teaching practice in the classrooms has a positive impact on teaching Fiqh in religious schools. As a recommendation, religious teachers need to constantly expand their pedagogical content knowledge from time to time so that they can implement effective teaching.